Financial Management Implementation and Good University Governance in Muhammadiyah Higher Education Institutions in South Sulawesi - Liya Saputri; Asrijal Bintang; Kahar; Irwan Abdullah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Financial management is a crucial foundation for implementing Good University Governance in private faith-based higher education institutions, particularly in Muhammadiyah Higher Education Institutions in South Sulawesi. This study aims to examine how financial management is implemented, how transparency, accountability, and participation are practiced, and how institutional efforts support governance improvement within Muhammadiyah higher education. This study employed a descriptive qualitative approach involving selected Muhammadiyah Higher Education Institutions in South Sulawesi. Data were collected through interviews, document analysis, and observation, focusing on financial planning, budgeting, implementation, reporting, accountability, and compliance with Muhammadiyah financial management guidelines. The findings show that the studied institutions have generally implemented financial management according to formal Muhammadiyah guidelines. Financial planning and budgeting are conducted through institutional mechanisms, while transparency and participation have been applied through internal communication, budget discussions, and involvement of relevant institutional units. However, accountability remains the most challenging dimension. Delays in financial reporting, limited human resource competence, uneven financial literacy, and inadequate information technology systems reduce the effectiveness of financial accountability. The discussion indicates that Good University Governance in Muhammadiyah higher education requires not only formal rules but also professional financial personnel, integrated digital systems, internal supervision, and institutional commitment to transparency and accountability. This study contributes to the literature by highlighting the hybrid nature of financial governance in faith-based private higher education, where formal governance principles, religious values, organizational guidelines, and institutional capacity interact. Strengthening financial governance is essential for improving public trust, institutional credibility, and long-term sustainability.